Determination of Flood Inundation Maps: A Case Study of Akyazi Industrial Zone - Osman Sönmez; Tuğçe Hırca (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Heavy and sudden rainfalls, snow melt, meteorological factors, human impact and climate change cause floods that lead to loss of life and property. Trend analysis shows that the number of floods has increased in recent years. The use of flood plains as a residental area or industrial area causes an increase in the potential impact of floods. Loss of life and property may ocur in a probable flood due to the presence of factories in the Akyazı industrial zone, which is one of the most affected zones by floods, and 1000-1500 people working actively in these factories.Therefore, flood protection wall was built by DSI for this zone. The aim of this study is to create a 1-D flood model of the zone within the scope of the Project for rehabilitation. Kucucek Creek passes through the study area. Kucucek Creek consists of merging of 2 branches on the upstream of the industrial zone. These are called Kucucek Creek main branch and Karaca Creek. In the study, ArcGIS 10.2 program was used to digitize the zone. In the hydraulic analyzes performed with 8 return period flood flows, it was determined that the repetition years will not occur flood and the rehabilitation project will be effective.